Pengaruh Nisbah Dan Suhu Pencampuran Terhadap Karakteristik Campuran Aspal Karet Alam Kompo (Cup Lump) - Yanny Sartika; Irdoni Irdoni; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Asphalt modified polymer (AMP) is used to increase the resistance of asphalt to changes in temperature by increasing the stiffness of the binder/binder at high temperatures and reducing stiffness at low temperatures at the same time. This study aims to study the effect of ratio and temperature of rubber cup lump on the characteristics of asphalt and determine the ratio and temperature of the best rubber cup lump for the manufacture of asphalt modified polymer. The asphalt used type of bitumen pen 60/70 Pertamina. Asphalt modified polymer is made by mixing cup lump with asphalt at a mixing temperature of 150 oC and 170 oC for 30 minutes. Cup lump ratio varied by 4%, 6%, 8%, 10% and 12%. Testing for modified asphalt includes parameters: penetration, softening point, weight loss and stability of the Marshall. Testing is in accordance with the 2012 Bina Marga General Specifications standard. Based on the research results obtained, the best ratio and temperature is 12% and mixing temperature 170 oC with a penetration value of 52.4 dmm, softening point of 63.55 oC, weight loss of 0.068 and the stability of the Marshall is 1904.4 kg.Keywords: asphalt modified, cup lump, ratio, stability, temperature